Assessment, Ujrah, and Promotion Influence on Islamic Gold Pawn Decisions in Baturaja - Riani, Diska; Any Eliza; Ahmad Hazas Syarif (Penerbit Goodwood, 2025)
Purpose: This study aims to analyze the influence of estimated value, ujrah (service fee), and promotional activities on the use of Islamic gold pawn (rahn) financing products at the Baturaja Islamic Pawnshop. Design/methodology/approach: This study investigates the partial and simultaneous effects of these variables and identifies the most dominant factor influencing customer decisions. Methodology/approach: This research employs a descriptive quantitative method using primary data collected through questionnaires distributed to 98 respondents who are active customers of Pegadaian Syariah Baturaja. Additional data were obtained from documentation and observations. The sampling technique used was purposive sampling, applying the Slovin formula with a 10% margin of error. Data analysis was conducted using multiple linear regression with SPSS version 25. Results/findings: The results indicate that the estimated value, ujrah, and promotion each have a positive and significant effect on the use of Islamic gold pawn financing products. Simultaneously, the three variables significantly influenced customers’ decisions to choose the rahn product. The adjusted R-square value of 0.826 demonstrates that 82.6% of the variance in product usage can be explained by these variables. Conclusions: The findings suggest that higher estimated values, lower ujrah, and more effective promotional efforts positively impact customer interest in Islamic gold pawn products. Limitations: This study was limited to one branch, potentially affecting its generalizability across different regions. Contribution: The findings provide valuable insights for improving marketing strategies and expanding customer engagement with Islamic financial products, particularly Rahn.